PENGARUH LITERASI KEUANGAN SYARIAH DAN SHARIAH GOVERNANCE TERHADAP KEPUTUSAN MAHASISWA DALAM BERINVESTASI DI PASAR MODAL SYARIAH - Patonatu Vikria; Efni Anita; Neneng Sudharyati (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research aims to analyze the influence of sharia financial literacy and sharia governance on students' decisions to invest in the sharia capital market. The objects of this research are members of the GIS (Sharia Investment Gallery) Faculty of Islamic Economics and Business, Sulthan Thaha Saifuddin State Islamic University, Jambi. The method used is multiple linear regression analysis with data processing using SPSS version 27. The independent variables in this research are sharia financial literacy and sharia governance, while the dependent variable in this research is students' decisions to invest in the sharia capital market. The results of the research show that the independent variables (Sharia financial literacy and Sharia governance) simultaneously have a significant effect on student decisions. Then, partially sharia financial literacy and sharia governance also have a significant influence on students' decisions to invest in the sharia capital market.